(untitled) (Zoological Records and Reviews, 2024)
Seasonal variation in temperature, precipitation, and resource availability drives predictable temporal fluctuations in animal community structure across terrestrial and aquatic ecosystems. This study quantified seasonal shifts in species richness, abundance, diversity indices, and guild composition across four animal communities – ground-dwelling beetles (Coleoptera: Carabidae), breeding birds, stream macroinvertebrates, and small mammals – sampled monthly across four seasons at three paired land-use sites (semi-natural grassland, managed cropland, riparian woodland) in northern Italy and central Austria between January 2022 and December 2023 (n = 14,832 individual records across 284 taxa). Species richness peaked in summer across all four groups (mean increase over winter baseline: +68.4% for carabids, +112.3% for birds, +44.1% for macroinvertebrates, +38.7% for small mammals). Shannon diversity (H’) showed the strongest seasonal signal in breeding birds (summer H’ = 2.84 +- 0.18 vs. winter H’ = 1.31 +- 0.14; paired t(8) = 11.42, p < 0.001). Multivariate community composition (NMDS on Bray-Curtis dissimilarity) revealed significant season x land-use interaction effects for all four groups (PERMANOVA F >= 3.8, p <= 0.002), indicating that land-use context modulates the magnitude of seasonal turnover. Indicator species analysis identified 47 taxa as season-specific indicators, with semi-natural grassland supporting 2.8x more seasonal indicator species than cropland. These findings underscore the importance of retaining structurally diverse habitats within agricultural landscapes to buffer animal community seasonality and maintain year-round biodiversity.